Analysis of selected choral works by John Tavener with particular reference to the post-1977 works - Imrie, Sally (Rhodes University, Faculty of Humanities, Department of Music and Musicology, 1998)
This thesis deals with sacred choral music written by John Tavener, a British composer born in 1944. It touches briefly on the background of Tavener and his early works (i.e. from about 1960-1976) - two works from that period have been selected for analysis, Celtic Requiem and Nomine Jesu. The main body of the thesis is concerned with those works composed,.after 1977, which show the influence of the Orthodox Church and Byzantine hymnography on Tavener's stylistic development. The selected works from this period to be analysed are: Ode of St Andrew of Crete, Two Hymns to the Mother of God, Magnificat, Nunc Dimittis, The Uncreated Eros, Eonia and We Shall See Him As Heis.
Keywords: Tavener, John; Choral music